Symbolika „Solidarności” w kampanii wyborczej do Sejmu w roku 2011 w okręgu wyborczym nr 25. Przykład uprawiania polityki symbolicznej na polskiej scenie politycznej - Szuta, Agnieszka (Polityka i Społeczeństwo, 2021)
The issue of the harnessing of symbols by politicians is essential, because it ex-plains to what extent government representatives are able to make an impact on society and how much identifying with specific symbols can be viewed as an acceptance of political myths and ideas by voters. This topic is particularly valid in the light of upcom-ing local government elections. Time caesuras of the analyzed subject will be limited by the duration of the election campaign that took place in 2011, from the announcement by the President of the Repub-lic of Poland to the start of electoral silence. Territorial coverage of the undertaken re-search will apply to constituency No. 25: the Gdańsk constituency which covers the following counties: Gdańsk, Kwidzyn, Malbork, Nowy Dwór, Starogard, Sztum, Tczew and cities with county rights like Gdańsk and Sopot. The intention of this article is to indicate the manner and intensity in which the symbol of “Solidarity” was used during the parliamentary election campaign by candi-dates from the Gdańsk constituency as well as to answer if, and to what extent it contrib-uted towards their electoral success.